The perplexing entity of rudimentary uterine horn: a case report of tertiary care center - Arvindar; Budaniya, Suman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Congenital uterine anomalies (CUAs) are an uncommon type of female genital malformations caused by abnormal development of Mullerian ducts during embryogenesis. Patients with an obstructive uterine anomaly have a higher risk of developing gynaecological and obstetric complications that may present at menarche or later in life. We present a case of severe dysmenorrhea in a adult reproductive age group women caused by obstructive hematometra in a noncommunicating horn of the unicornuate uterus. A differential diagnosis of a possible anomaly was made using 2-dimensional pelvic ultrasonography, which was later confirmed using MRI that revealed an anomalous uterine cavity with a single left-sided cornua communicating with the cervix and a distended right-sided rudimentary horn. She underwent a right salpingectomy and right oophorectomy with rudimentary horn excision (hemi-hysterectomy), which was successfully managed by laparotomy. This case emphasizes the importance of physicians being cognizant in identifying patients with uterine anomaly to provide appropriate treatment and prevent adverse reproductive outcomes.